The Epidemiology of IRIS in Southern India: An Observational Cohort Study. (September 2017) - Thambuchetty, Nisha; Mehta, Kayur; Arumugam, Karthika; Shekarappa, Umadevi G.; Idiculla, Jyothi; Shet, Anita
Immune reconstitution inflammatory syndrome (IRIS) is an uncommon but dynamic phenomenon seen among patients initiating antiretroviral therapy (ART). We aimed to describe incidence, risk factors, clinical spectrum, and outcomes among ART-naive patients experiencing IRIS in southern India. Among 599 eligible patients monitored prospectively between 2012 and 2014, there were 59.3% males, with mean age 36.6 ± 7.8 years. Immune reconstitution inflammatory syndrome incidence rate was 51.3 per 100 person-years (95% confidence interval: 44.5-59.2). One-third (31.4%) experienced at least 1 IRIS event, at a median of 27 days since ART initiation. Mucocutaneous infections and candidiasis were common IRIS events, followed by tuberculosis. Significant risk factors included age >40 years, body mass index <18.5 kg/m 2, CD4 count <100 cells/mm 3, viral load >10 000 copies/mL, hemoglobin <11 g/dL, and erythrocyte sedimentation rate >50 mm/h. Immune reconstitution inflammatory syndrome–related morality was 1.3% (8 of 599); 3 patients died of complicated diarrhea. These findings highlight the current spectrum of IRIS in South India and underscore the importance of heightened vigilance for anemia and treatment of diarrhea and candidiasis during ART initiation.